THE EMERGENCE AND PROSPECTS OF NEW TACTICAL METHODS OF UNITS IN BATTLE (COMBAT OPERATIONS) - Ibragimov Abrorbek Makhamadkomilovich (Web of Journals Publishing, 2024)
This article studies how new tactical methods of combat units were formed and their historical process. The factors, reasons for the emergence of new tactical methods, and their development in current armed conflicts are analyzed. The prospects for updating tactical methods in future battles are also considered.
Keywords: Tactics, units, combat operations, new methods, military technology, strategy, innovation.